REGULATION OF THE PROFESSION OF APP-BASED WORKERS (REMUNOM, 2023)
This article addresses the growing need to regulate the profession of app workers, such as rideshare drivers and food delivery couriers. The advancement of technology and the proliferation of app platforms have raised important questions regarding the rights, protections, and working conditions of these professionals. The aim of this article is to analyze the challenges and implications associated with regulating these emerging professions, in the context of a literature review study, including materials published on academic websites and in journals. The article begins by highlighting the economic significance of app workers in modern economies, as well as the flexibility these platforms offer to workers. However, concerns regarding job insecurity, social benefits, fair wages, and basic labor rights faced by many of these workers are also discussed. The challenges associated with regulation are examined in detail, including employment status determination, defining minimum benefits, protection against discriminatory platform practices, and the establishment of effective monitoring mechanisms. Furthermore, potential impacts of regulation on the economy are discussed, including the possibility of increased costs for app companies and implications for service prices. In conclusion, the article reflects on the importance of striking a balance between the flexibility provided by app platforms and the need to ensure fair and dignified working conditions for the workers. The regulation of the app workers' profession emerges as a complex challenge, with social, economic, and legal implications that must be carefully considered to promote a more equitable and sustainable work environment.